(2i+2)(4i-5)=0

Simple and best practice solution for (2i+2)(4i-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2i+2)(4i-5)=0 equation:


Simplifying
(2i + 2)(4i + -5) = 0

Reorder the terms:
(2 + 2i)(4i + -5) = 0

Reorder the terms:
(2 + 2i)(-5 + 4i) = 0

Multiply (2 + 2i) * (-5 + 4i)
(2(-5 + 4i) + 2i * (-5 + 4i)) = 0
((-5 * 2 + 4i * 2) + 2i * (-5 + 4i)) = 0
((-10 + 8i) + 2i * (-5 + 4i)) = 0
(-10 + 8i + (-5 * 2i + 4i * 2i)) = 0
(-10 + 8i + (-10i + 8i2)) = 0

Combine like terms: 8i + -10i = -2i
(-10 + -2i + 8i2) = 0

Solving
-10 + -2i + 8i2 = 0

Solving for variable 'i'.

Factor out the Greatest Common Factor (GCF), '2'.
2(-5 + -1i + 4i2) = 0

Factor a trinomial.
2((-1 + -1i)(5 + -4i)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-1 + -1i)' equal to zero and attempt to solve: Simplifying -1 + -1i = 0 Solving -1 + -1i = 0 Move all terms containing i to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1i = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1i = 0 + 1 -1i = 0 + 1 Combine like terms: 0 + 1 = 1 -1i = 1 Divide each side by '-1'. i = -1 Simplifying i = -1

Subproblem 2

Set the factor '(5 + -4i)' equal to zero and attempt to solve: Simplifying 5 + -4i = 0 Solving 5 + -4i = 0 Move all terms containing i to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4i = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4i = 0 + -5 -4i = 0 + -5 Combine like terms: 0 + -5 = -5 -4i = -5 Divide each side by '-4'. i = 1.25 Simplifying i = 1.25

Solution

i = {-1, 1.25}

See similar equations:

| 0.3+0.5x=2.3+x | | 144=3x+47+7x-13 | | 10=6+lnx | | -3(2x)= | | -560+(-40)=-600 | | -5n-4=-94 | | -5y+15=6 | | -3(5p+4)-2(4-11p)=3(9+2p) | | -5+15=6 | | 6x^2+11a+2=4 | | X=-120+59 | | 18a^2-10a+27a-15=0 | | -2a+3-a=0 | | 9=3a | | 4-2x-3=17 | | 3x-6y-7x+3y= | | 2z-9=21 | | 9(y+9)= | | -d=-2d+7 | | 4+2x+3=17 | | C+28=c+65 | | ((30)180)+((36)180)+((((8)9)6)36)+((((8)5)6)36)+((((8)7)7)36)+(18(7))+8500= | | 19+4(6c-1)= | | 4+2x-3=17 | | 8x-9=6x+29 | | (6i+5)-(-10i-5)=0 | | 4(3x-3)-2=4(x-4)+42 | | 3y-6y+2=8y+6-5 | | 3x+4/2=5/6 | | 8x^3-120=0 | | -8(3x+9)=15-7x | | 14x+8y=135 |

Equations solver categories